Mapping the potential human health implications of groundwater pollution in southern Sri Lanka - Rajasooriyar, L.D.; Boelee, Eline; Prado, M.C.C.M.; Hiscock, K.M. (Elsevier, 2013)
In southern Sri Lanka, irrigation influences the concentrations of faecal bacteria and inorganic toxic contaminants in groundwater. We develop a groundwater vulnerability map describing the potential human health implications of harmful constituents in the Uda Walawe Basin, by overlaying geological and land use data with information describing the irrigation system, the oxygen isotope composition of water bodies, and the concentrations of selected contaminants. Given the limited data available, we examine the spatial distribution of harmful constituents and the potential human health risks. Fluoride poisoning from groundwater is the greatest health threat in our study area, where fluoride concentrations ranging from 0.1 to 9.2 mg/L are associated with a geologic origin. Arsenic occurs in high concentrations, up to 0.4 mg/L, in areas with low recharge, although the source of arsenic is not clear. Nitrate concentrations are low, ranging from 0.4 to 23 mg/L, despite high fertilizer inputs, except in areas with low recharge and non-favourable reducing conditions, where concentrations up to 136 mg/L are found. Faecal bacteria decrease from surface water via shallow groundwater to deep groundwater. Irrigation water appears to play a major role in increasing microbial contamination and diluting inorganic constituents in groundwater. Hence, the most important determinants for mapping groundwater vulnerability are local geology and infiltration of irrigation water. The method we present provides a qualitative, yet practical, alternative to commonly used vulnerability mapping techniques for countries where high human health risk via consumption of groundwater is inevitable, and thus acts as a tool for selecting preventive and curative measures.